Boredom coping in the context of secondary education - Denisa Urbanova; Isabella Pavelkova (Czech Pedagogical Society, 2022)
The article concerns the problematics of the boredom experience and especially boredom coping in Czech secondary school students (n = 460). The relationships between, on the one hand, reported boredom frequency, various aspects of state boredom experienced at school, trait boredom, grade point average and learning motivational characteristics and, on the other hand, different types of boredom coping strategies have been examined. Data were obtained using the Boredom Proneness Scale, Multidimensional State Boredom Scale, Coping with Boredom Scale, Learning Motivation Inventory and closed questions. Descriptive and inductive statistics were used to process the data. More and less risky boredom coping strategies were identified with regard to the boredom experience at school and grade point average. A key factor facilitating adaptive boredom coping appears to be the capability to find personal value in potentially boring tasks and to exert cognitive effort together with high levels of positive achievement motivation and conscientiousness with regard to schoolwork. Additionally, at least a certain level of cognitive motivation, which seems to be a key supportive factor, is needed. A risk factor with regard to rather maladaptive boredom coping appears to be the tendency to systematically employ avoidance or even escaping behavior. The results indicate that school boredom coping issues are very complicated and have numerous implications for further research.